Jesus Christ as Social Philosopher: The Inclusive Sociability and Its Implications for Christians in Indonesia - Nole, Otniel Aurelius; Molewe, Adlan Christember (Litbang STFT Widya Sasana Malang, 2025)
In a nation of diverse beliefs like Indonesia, there can never be enough discourse on articulating ways to pursue peace. This article proposes that reimagining Jesus Christ as a social philosopher with inclusive sociability is crucial in motivating Christians’ social attitudes in public spheres in Indonesia. As the central figure of the Christian faith, this constructive imagination is particularly relevant in Indonesia, where the “what would Jesus do” religiosity is prominent. To analyse and construct Jesus as a social philosopher with inclusive sociability, this article utilises two approaches: content analysis and conversation analysis. The research finds that, as a social philosopher, Jesus exhibits a capacity for critical reasoning accompanied by a humanising attitude. This is evident in how He interacts across cultures, accepts sociocultural differences, and embodies unconditional love, unlimited forgiveness, and selfless humility. This research presents a critical model for Indonesian Christians to pursue friendships and relational harmony amidst differences, based on an ethic of empathy.